NEUROPSYCHOLINGUISTIC FEATURES OF SMILE AND LAUGHTER IN NONVERBAL SPEECH - Radjabovich, Bobokalonov Ramazon; qizi, Ermatova Zulfizar Jamoliddin (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
In the foreground are many secrets and principles of language and speech. Language and speech together are a topic of common use. All their principles are equally important, because in the relationship between language and speech. Because speech is also a source of energy in the management of the mind. A smile also relaxes the human brain. It nourishes the human psyche and renews its spiritual world. A smile is a very delicate matter, one must know its place and learn how to give it to someone. In the background: gestures, facial expressions, expressive signs of facial expressions in international culture - looking with the eyes, moving eyebrows, twisting lips, shaking the head, showing the tongue, running a long finger between the two lips, etc. Learning neuropsycholinguistics also helps to study the subtle aspects of smiling. This is one of the practically unsolved problems of neuropsycholinguistics.